Answer:
y/x = 2.5
Step-by-step explanation:
y ∝ x
change ∝ to = by adding constant k or c
y = kx
Divide both sides by x
y/x = k, also k = y/x
Input the values
k = (7 1/2)/3. Change 7 1/2 to improper fraction to give 15/2
k = (15/2)/3
k = ÷ 3
Change the division sign to multiplication which will change 3 to its inverse(1/3)
k = ×
k =
Divide the numerator and denominator by 3 to get 5/2
k = 5/2
From y/x = k,input k into the eqn
y/x = 5/2
y/x = 2.5
Answer:
We conclude that:
(gºf)(4) = g(f(4)) = g(6) = 6
Step-by-step explanation:
Given
We have to determine (gºf)(4).
(gºf)(4) = g(f(4))
f(4) = 2(4)-2
= 8 - 2
= 6
Thus,
(gºf)(4) = g(f(4)) = g(6) = 6
Therefore, we conclude that:
(gºf)(4) = g(f(4)) = g(6) = 6
<span>∠BCA = 120 /2 = 60
answer
</span><span>∠BCA</span>
<span>Brenda would be correct, another way to find the answer would be to use the keep change flip method. Where you keep 5/2 change division to multiplication then flip 4/1.
The equation would then be 5/2 * 4/1 then you just multiply straight across 5*4 = 20 and 2*1 equals 2. You end up with 20/2 which reduces to 10</span>
Answer:
3/4 is what you are adding
17/4+3/4=20/4=5